2017
DOI: 10.1002/jcop.21883
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring program practices as predictors of match longevity

Abstract: Mentoring has been shown to have a small to moderate effect on youth outcomes; however, implementation of research‐based practices improves program efficacy. Benchmark program practices and Standards in the Elements of Effective Practice for Mentoring (MENTOR, 2009) were assessed in the current study as predictors of match longevity. Secondary data analyses were conducted on a national agency information management database from 45 Big Brothers Big Sisters agencies and 29,708 matches from across the U.S. Agenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 21 publications
5
37
0
1
Order By: Relevance
“…A subset of programs represented in the AIM dataset was recruited for the project as part of a larger study on program practice implementation, in which program staff completed a supplemental survey about program practices. An in‐depth description of the broader dataset and study protocol is available in Kupersmidt et al (). Main analyses were conducted on foster youth from the participating programs subset, which included 32 BBBS agencies serving 208 youth in foster care.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A subset of programs represented in the AIM dataset was recruited for the project as part of a larger study on program practice implementation, in which program staff completed a supplemental survey about program practices. An in‐depth description of the broader dataset and study protocol is available in Kupersmidt et al (). Main analyses were conducted on foster youth from the participating programs subset, which included 32 BBBS agencies serving 208 youth in foster care.…”
Section: Methodsmentioning
confidence: 99%
“…Program practices were assessed using a shortened version of the Elements Quality Improvement Process online program self‐assessment questionnaire consisting of 31 items (Kupersmidt et al ). Responses were combined into 22 practices, based upon those included in the Third Edition of the EEPM (MENTOR, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, because mentoring is essentially a relationship‐based intervention, it can ignite vulnerabilities and elicit behavioral patterns that were previously established in their bonds with their incarcerated parent. With implementation of high‐quality practices and appropriate program enhancements, however, staff and volunteer mentors can be better equipped to meet the relational and behavioral challenges posed by youth in special populations such as COIP (Kupersmidt & Rhodes, ; Kupersmidt, Stump, Stelter, & Rhodes, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a qualitative study of mentoring COIP, mentors reported that the pre‐match training that they received was insufficient (Merenstein et al., ). However, pre‐match mentor training of adequate duration, quality, and content has been associated with longer matches (Kupersmidt, Stump, Stelter, & Rhodes, ). Adequately trained mentors are more knowledgeable about mentoring, have greater clarity about relationship boundaries, better understand the roles necessary to be effective mentors, and feel more prepared to be in a mentoring relationship (Kupersmidt, Stelter, Rhodes, & Stump, ).…”
Section: Introductionmentioning
confidence: 99%